Leptospira kmetyi sp. nov., isolated from an environmental source in Malaysia. - Slack, Andrew T.; Bejo, Siti Khairani; Symonds, Meegan L.; Dohnt, Michael F.; Galloway, Renee L.; Steigerwalt, Arnold G.; Bahaman, Abdul Rani; Craig, Scott; Harrower, Bruce J.; Smythe, Lee D. (Society for General Microbiology, 2009)

(untitled)
A single Leptospira strain (designated Bejo-Iso9T) was isolated from a soil sample taken in Johor, Malaysia. The isolate showed motility and morphology typical of the genus Leptospira under darkfield microscopy. Cells were found to be 10–13 mm in length and 0.2 mm in diameter, with a wavelength of 0.5 mm and an amplitude of approximately 0.2 mm. Phenotypically, strain Bejo- Iso9T grew in Ellinghausen–McCullough–Johnson–Harris medium at 13, 30 and 37 6C, and also in the presence of 8-azaguanine. Serologically, strain Bejo-Iso9T produced titres towards several members of the Tarassovi serogroup, but was found to be serologically unique by cross-agglutinin absorption test and thus represented a novel serovar. The proposed name for this serovar is Malaysia. Phylogenetic analysis of 16S rRNA gene sequences placed this novel strain within the radiation of the genus Leptospira, with sequence similarities within the range 90.4–99.5% with respect to recognized Leptospira species. DNA–DNA hybridization against the three most closely related Leptospira species was used to confirm the results of the 16S rRNA gene sequence analysis. The G+C content of the genome of strain Bejo-Iso9T was 36.2 mol%. On the basis of phenotypic, serological and phylogenetic data, strain Bejo-Iso9T represents a novel species of the genus Leptospira, for which the name Leptospira kmetyi sp. nov. is proposed. The type strain is Bejo-Iso9T (5WHO LT1101T5KIT Bejo-Iso9T).